Pancreatic insulinomas: Laparoscopic management. - Antonakis, Pantelis T; Ashrafian, Hutan; Martinez-Isla, Alberto (World J Gastrointest Endosc, 2015)
Insulinomas are rare pancreatic neuroendocrine tumors that are most commonly benign, solitary, and intrapancreatic. Uncontrolled insulin overproduction from the tumor produces neurological and adrenergic symptoms of hypoglycemia. Biochemical diagnosis is confirmed by the presence of Whipple's triad, along with corroborating measurements of blood glucose, insulin, proinsulin, C-peptide, β-hydroxybutyrate, and negative tests for hypoglycemic agents during a supervised fasting period. This is accompanied by accurate preoperative localization using both invasive and non-invasive imaging modalities. Following this, careful preoperative planning is required, with the ensuing procedure being preferably carried out laparoscopically. An integral part of the laparoscopic approach is the application of laparoscopic intraoperative ultrasound, which is indispensable for accurate intraoperative localization of the lesion in the pancreatic region. The extent of laparoscopic resection is dependent on preoperative and intraoperative findings, but most commonly involves tumor enucleation or distal pancreatectomy. When performed in an experienced surgical unit, laparoscopic resection is associated with minimal mortality and excellent long-term cure rates. Furthermore, this approach confers equivalent safety and efficacy rates to open resection, while improving cosmesis and reducing hospital stay. As such, laparoscopic resection should be considered in all cases of benign insulinoma where adequate surgical expertise is available.